Pengaruh Spesies Zingiberaceae (Jahe, Temulawak, Kunyit, dan Kunyit Putih) dan Keetbalan Isiran Sebelum Pengeringan terhadap Kadar dan Aktivitas Antioksidan Ekstrak Aseton yang Dihasilkan - Aisyah Tri Septiana; Mustaufik Mustaufik; Hidayah Dwiyanti; Deddy Muchtadi; Fransiska Zakaria; Maria Menu Ola (agriTECH, 2006)
This research was aimed to determine the influence ofzingiberaceae species and the influence ofslice thickness before drying process by using cabinet dryer to the antioxidant content (total phenolics and curcumin) and antioxidant activity (absorbance of peroxide and malonaldehide ). The results of the research showed that total phenolics of turmeric extract (216.57 ppm) and temulawak (190.41 ppm) > ginger (127,97 ppm) > white turmeric extract (31,13 ppm), where as curcumin content of turmeric (55,93 ppm) and temulawak extract (48,95 ppm) > white turmeric (6,51 ppm) and ginger extract (4,67 ppm). The antioxidant activity that is indicated peroxide and malonaldehide forming from 1 inoleic acid which is supplemented to temulawak extract, turmeric, and ginger extract > white turmeric extract. Turmeric, temulawak, and ginger extract had the antioxidant activity higher than tocopherol, where as white turmeric had lower antioxidant activity than a tocopherol. The slicing sample with slice size of 4 mm before drying process with cabinet dryer had rate and antioxidant activity better than that of 2 mm. The total phenolics of zingiberaceae extract with slice size of 4 mm (161,86 ppm) > 2 mm (121,18 ppm), and the curcumin content of zingiberaceae extract with slice of 4 mm (34,58 ppm) > 2 mm (23,45 ppm). The slice of 4 mm had a relatff higher value than the slice of 2 mm to the antioxidant activity zingiberaceae extract that is indicated peroxide and malonaldehide formation.